The association of hyponatremia, risk of confusional state, and mortality: a prospective controlled longitudinal study in older patients - Zieschang, Tania; Wolf, Marcia; Oster, Peter; Uhlmann, Lorenz (Deutsches Ärzteblatt, 2016)
With a prevalence of 15-30%, hyponatremia is the most common electrolyte abnormality in hospital inpatients (1-3). Geriatric patients are a high-risk group because of their changed physiology, multimorbidities, and polypharmacy (4). In older persons,...